A relation between sequences generated by Golomb’s preference algorithm - Jiang, Yupeng (Designs, codes, and cryptography, 2023)
In a recent paper (DCC, Rubin and Weiss in 85:547–555, 2017), based on the differentiation operator, Rubin and Weiss proposed a mapping of the binary prefer-opposite de Bruijn sequence of order n onto the binary prefer-one de Bruijn sequence of order n - 1 . Both prefer-opposite and prefer-one de Bruijn sequences can be regarded as special cases of sequences generated by Golomb’s preference algorithm. In this paper, we introduce inertia function in Golomb’s preference algorithm, and then applying it to extend Rubin and Weiss’s result to more general cases.